Application of The Brain-Based Learning Model on Students' Learning Outcomes and Initial Mathematical Abilities - Ibnu Imam Al Ayyubi; Sofia Martini; Ai Sri Masfuroh; Aulia Suwanti Nur Ramdani (TADRUSUUN: JURNAL PENDIDIKAN DASAR, 2024)
Along with advances in technology and understanding of the learning process, the Brain learning model emerged Based Learning is one of the innovative steps in improving the quality of learning. This research aims to see whether some differences and interactions occur in student learning outcomes which that implications for students' initial mathematical abilities and the basic competencies learned by students. This research was carried out at SDN Batujajar 3 with a quantitative approach. This research method uses survey methods and ANOVA test analysis to see the relationship between mathematics learning outcomes using the BBL model, Basic Competencies consisting of KD 3.3, KD 3.4, and KD 3.5, and students' Initial Mathematical Ability with high, medium, and low classifications. This research instrument uses a test to test the data analysis requirements used, consisting of a normality test using Kolomogorov-Smirnov and a homogeneity test assisted by SPSS version 26. In this study, it was found that there were differences in students' mathematics learning outcomes using the brain learning model-based learning on the basic competencies learned by students and students' initial mathematical abilities, but there is no significant interaction between them. This shows that there is a significant difference in students' mathematics learning outcomes between KD 3.3 and 3.4 and 3.3 and 3.5, but this does not happen at KD 3.4 and 3.5. Apart from initial mathematical abilities, students in the categories of high and medium, high and low, and medium and low obtained significant differences between the three. Thus, it is hoped that further research can have implications for students' level of cognition and geography regarding mathematics learning outcomes using the brain learning model-based learning.